2016
DOI: 10.1186/s12943-015-0489-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low doses of actinomycin D on neuroblastoma cell lines

Abstract: BackgroundNeuroblastoma is a malignant embryonal tumor occurring in young children, consisting of undifferentiated neuroectodermal cells derived from the neural crest. Current therapies for high-risk neuroblastoma are insufficient, resulting in high mortality rates and high incidence of relapse. With the intent to find new therapies for neuroblastomas, we investigated the efficacy of low-doses of actinomycin D, which at low concentrations preferentially inhibit RNA polymerase I-dependent rRNA trasncription and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
103
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(109 citation statements)
references
References 49 publications
4
103
1
1
Order By: Relevance
“…3C) piR-23662 (15 fold, p < 0.003), piR-26526 (10 fold, p < 0.00003), piR-26527 (9 fold, p < 0.00009), piR-30293 (9 fold, p < 0.00009) and piR-26528 (8 fold, p < 0.000008) in TNBC compared to normal tissue. Recent studies have also reported the involvement of specific piRNAs in different cancers, for example, piR-4987, piR-20365, piR-20485, piR-20582 and piR-932 in breast cancer 57, 58, piR-823 and piR651 in gastric cancer 59, 60, upregulated piR-32051, piR-39894, piR-43607 and downregulated piR-38756, piR-57125, piR-30924 in kidney cancer 61, piR-Hep1 in liver cancer 62, downregulated piR-017061 in pancreatic cancer 63, downregulated piR-823 in multiple myeloma, downregulated piR-L-163 in lung cancer 64, and piR-59056, piR-32105 and piR-58099 in colon cancer 65. Analyzing stage-wise differential expression of piRNAs, we found 46 piRNAs were shared between stages I & II; three shared piRNAs in stage II & III whereas no common piRNAs in stages I & III.…”
Section: Resultsmentioning
confidence: 99%
“…3C) piR-23662 (15 fold, p < 0.003), piR-26526 (10 fold, p < 0.00003), piR-26527 (9 fold, p < 0.00009), piR-30293 (9 fold, p < 0.00009) and piR-26528 (8 fold, p < 0.000008) in TNBC compared to normal tissue. Recent studies have also reported the involvement of specific piRNAs in different cancers, for example, piR-4987, piR-20365, piR-20485, piR-20582 and piR-932 in breast cancer 57, 58, piR-823 and piR651 in gastric cancer 59, 60, upregulated piR-32051, piR-39894, piR-43607 and downregulated piR-38756, piR-57125, piR-30924 in kidney cancer 61, piR-Hep1 in liver cancer 62, downregulated piR-017061 in pancreatic cancer 63, downregulated piR-823 in multiple myeloma, downregulated piR-L-163 in lung cancer 64, and piR-59056, piR-32105 and piR-58099 in colon cancer 65. Analyzing stage-wise differential expression of piRNAs, we found 46 piRNAs were shared between stages I & II; three shared piRNAs in stage II & III whereas no common piRNAs in stages I & III.…”
Section: Resultsmentioning
confidence: 99%
“…Mature forms of these RNAs associate with biogenesis pathway proteins such as Argonaute (AGO) class of proteins: miRNAs and siRNAs with AGO proteins and piRNAs with PIWI proteins [25] to guide target specific gene regulation [6, 7]. Gene regulation exerts control at transcriptional and post-transcriptional levels and piRNAs, in association with PIWI proteins, are involved in both levels [8, 9]. For a long time, the only roles of PIWI proteins were believed to be in the regulation of transposons and [10] in the maintenance and development of germinal stem cells [11]; however, the functions of piRNAs and PIWI proteins as epigenetic regulators have started to emerge [1, 12].…”
Section: Introductionmentioning
confidence: 99%
“…It is increasingly being recognized that the sequence based complementarity may not be restricted to 3′ UTR and may expand to 5′UTR, the coding sequence or even the introns [20]. Given the diverse functions of piRNAs and PIWI proteins, it is evident that these molecules may also contribute to tumorigenesis [9]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the treatment with ActD as well as the treatment at the lower dissociation temperature led to lower viability, the change was statistically insignificant relative to the control. However, we expected that the administration of ActD would lead to an increase in the number of dying cells (its toxic effect published by Cortes et al (2016)), and subsequently to lower cell 7 yield. Surprisingly, the yield was comparable or even higher during dissociation at 37 °C ( Figure 4B).…”
Section: The Effect Of Different Temperature On the Cell Quality Andmentioning
confidence: 99%